2015
DOI: 10.1016/j.rser.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ willingness to pay for enhanced construction waste management: A Hong Kong study

Abstract: a b s t r a c tBased on the polluter pays principle, construction waste disposal charging schemes (CWDCS) have been deployed by various economies as one of the most effective ways of managing construction waste. Nevertheless, a means of rationalizing these schemes has not been well documented. Using the economic technique of contingent valuation method (CVM), this study aims to investigate stakeholders' willingness to pay (WTP) for enhanced construction waste management (CWM) with a view to providing a scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…The method has been applied to assess the value for renewable energy [44], forests [15], wetlands [45], watersheds [17], hydrogen buses [46] and other nonmarket resources [47,48]. The induction modes for willingness to pay include open, repeat bidding, dichotomy, payment card, and so on [49], which are increasingly used to obtain the residents' WTP for environmental protection of the river basin. The payment card of the induction mode has the advantages of easy access to the respondents' willingness to pay, avoidance information deviation, and circumvention extreme values [17].…”
Section: Contingent Valuation Methodsmentioning
confidence: 99%
“…The method has been applied to assess the value for renewable energy [44], forests [15], wetlands [45], watersheds [17], hydrogen buses [46] and other nonmarket resources [47,48]. The induction modes for willingness to pay include open, repeat bidding, dichotomy, payment card, and so on [49], which are increasingly used to obtain the residents' WTP for environmental protection of the river basin. The payment card of the induction mode has the advantages of easy access to the respondents' willingness to pay, avoidance information deviation, and circumvention extreme values [17].…”
Section: Contingent Valuation Methodsmentioning
confidence: 99%
“…To use a value of WTA from the literature is seldom possible; on the contrary, a different value should be used for different municipalities, since social factors significantly influence the value in question [61]. Numerous other case studies can be found in the literature; herein we refer to [62][63][64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Sumber: Hasil penelitian 2018, diolah (Han et al, 2019:190;Noviati Sadikin, Mulatsih, Pramudya Noorachmat, & Susilo Arifin, 2017;Merryna, 2009;Lu, Peng, Webster, & Zuo, 2015) (Annisa, 2015) dalam penelitiannya menemukan dengan uji parsial (uji t) pendapatan memiliki pengaruh paling nyata terhadap WTP, tetapi pendidikan dan jumlah anggota keluarga tidak memiliki pengaruh nyata terhadap WTP pengelolaan sampah rumah tangga. juga dengan variabel jumlah anggota keluarga dengan tingkat kepercayaan 95% tidak mempunyai pengaruh yang signifikan terhadap WTP sampah rumah tangga di Kelurahan Simpang Baru Panam.…”
Section: Tabel 3 Jumlah Responden Yang Tidak Bersedia Dan Bersedia Bunclassified